Policy Analysis of Booster Vaccination against State-Owned Pharmaceutical Stocks - Mohammad Arridho Nur Amin (Jurnal Ekonomi Lembaga Layanan Pendidikan Tinggi Wilayah I, 2023)
Medical devices became one of the most important and most sought after things during the Covid-19 pandemic. This will certainly have an impact on the pharmaceutical stock price, this study discusses the reaction of the share price of state-owned companies in the pharmaceutical sector before and after the implementation of booster vaccination. The announcement of the booster vaccination recana also affected the performance of shares of PT. Indofarma and PT. Kimia Farma as a vaccine development company at the beginning of the pandemic. In this study using comparative descriptive methods, data taken in the form of daily stock data obtained on the Indonesia Stock Exchange website and yahoo finance website. Based on studies that have been conducted on existing data, the results of the analysis obtained data that there was an abnormal return negative both in INAF and KAEF before and after the implementation of booster vaccination but abnormal return positive also occurred a few days after the implementation of booster vaccination, tva experienced an increase in shares even though a few days before and after the booster vaccination of INAF and KAEF shares experienced abnormal negative returns.